(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In Republic of Karelia tourism accepted to be one of priority orientations in program on socio-economic development of region. This paper observes recreation potential of Republic Karelia. More emphasis is put on to Zaonezhje as an area with rich history and unique natural complexes. We developed a water route around islands of northern part of Onego Lake. It can become a good alternative tourist product and will be able to reduce recreation load on another popular destinations. This route can be used in school educational program also.